Linkages from agricultural growth in Kenya - Bigsten, Arne; Collier, Paul (International Food Policy Research Institute, 1995)
Kenya is an exciting case for those who suspect that agriculture has powerful linkages with the rest of the economy. Over the period 1965-87 Kenya's agricultural production consistently surpassed the average for Sub-Saharan Africa. The same was true of its manufacturing and services (see World Bank 1989, table 7.1). One possible explanation for this performance is that agricultural growth stimulated growth in the other sectors of the economy. Such a hypothesis is a priori plausible because Kenya's government policy, in contrast to that of other African governments, was not heavily biased against agriculture. Thus, it makes more sense to attribute the country's good agricultural performance to pro-agricultural policy than to attribute its good industrial performance to pro-industrial policy. It appears that Kenya's policy had an exogenous influence that tended to favor agriculture, and this partiality generated indirect benefits for the rest of the economy. Elsewhere in Africa, policy heavily favored industry and services, but any indirect benefits from these sectors to agriculture were evidently negligible. The situation in Kenya suggests that a pro-agriculture policy not only promotes agricultural growth but also helps industry and services achieve faster growth than they would if those sectors were favored.